Rashtriya Barh Ayog (National Commission on Floods) Report Volume-II (Appendices) - Planning Commission (Planning Commission, 1980)
Man has had to live with floods since the very beginning. Efforts have been made from early times to give protection to land and property. These early attempts catered to individual needs for protection to small areas. Prior to 1954, about 5,300 km of embankments were constructed by Governmental agency, largely for the protection of irrigated areas in the north and deltaic tracts of the east flowing rivers in the south. These afforded protection to an area of about three million hectares.
Government of India Ministry of Energy and Irrigation (Department of Irrigation)
Government of India Ministry of Energy and Irrigation (Department of Irrigation)